Behavioural Biases in Investment Decisions:An Exploration of the Role of Gender - Singh, Harsh Pratap; Goyal, Nisha; Kumar, Satish (Indian Journal of Finance, 2016)
Classical finance theories are based on the assumption of rational decision making. However, it has been concluded by various researchers that in practical situations, humans are not fully rational. They are influenced by various behavioural factors and errors in judgment while making decisions. These behavioural factors, also termed as cognitive illusions, cannot be adequately explained by traditional finance theories. This research work sought to assess the impact of gender on certain identified behavioural factors (or biases) such as overconfidence bias, reference point bias, self-attribution bias, framing effect bias, overreaction bias, and regret avoidance bias in investment decision making of individual investors. A sample survey of 521 individual investors was conducted through a structured questionnaire in the National Capital Region of India. The results of detailed investigation of collected data revealed clearly that individuals’ investment decisions are not fully rational. Investors were found to be prone towards behavioural biases tested in this study. However, mix evidence was found in the study about variation in the propensity to exhibit these behavioural biases between male and female investors. Gender effect was found to be statistically significant in case of overconfidence bias, self-attribution bias, and regret avoidance bias.